2016
DOI: 10.1097/mpa.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-21 and miRNA-34a Are Potential Minimally Invasive Biomarkers for the Diagnosis of Pancreatic Ductal Adenocarcinoma

Abstract: Serum miR-21 and miR-34a are potentially useful diagnostic biomarkers of PDAC. In addition, our results suggest that these miRNAs are not differentially expressed in saliva, making them unsuitable for use as noninvasive biomarkers for diagnostic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 54 publications
0
61
0
Order By: Relevance
“…A previous study proposed that miR-34a is a potentially useful marker for the diagnosis of PDAC [8]. Our study demonstrated that lower miR-34a levels correlate with severe clinical symptoms and poor prognosis in PDAC patients.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…A previous study proposed that miR-34a is a potentially useful marker for the diagnosis of PDAC [8]. Our study demonstrated that lower miR-34a levels correlate with severe clinical symptoms and poor prognosis in PDAC patients.…”
Section: Discussionmentioning
confidence: 47%
“…However, most of the functional roles and targets of miRNAs have not been identified. Reduced expression of miR-34a is associated with poor overall survival in PDAC patients following resection [7] and serum miR-34a levels are potential diagnostic biomarkers of PDAC [8]. Exogenous overexpression of miR-34a inhibits the proliferation of cultured pancreatic cancer cells [9], sensitizes MiaPaCa2 pancreatic cancer cells to chemo- and radiotherapy by downregulating Bcl-2, Notch1 and Notch2 expression [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, miR-34a was found to be up-regulated in the serum of patients with PDAC. 155 The results obtained from the GEO database (accession numbers: GSE32688 and GSE15471) also indicated that miR-34a expression in PC was up-regulated. 156,157 The Role of miR-34a in the Proliferation of PC Several studied have explored the relationship between miR-34a and the proliferation of PC cells.…”
Section: Mir-34a Expression In Pcmentioning
confidence: 96%
“…The results showed that the expression level of miR-34a was closely related to the clinicopathological features of patients, suggesting that miR-34a may be used as a biomarker for the diagnosis and prognosis of PDAC. 155 Furthermore, CpG methylation of miR-34a was also employed as a diagnostic indicator for the prognosis of patients with PC. 164 Akamatsu et al 165 found that the expression level of miR-34a in serum could be used as a biomarker to distinguish between PDAC and autoimmune pancreatitis (AIP).…”
Section: The Role Of Mir-34a In the Diagnosis And Prognosis Of Pcmentioning
confidence: 99%
“…The role of miR-34a in regulating tumor biology has been extensively studied, while being an effective biomarker is another function of miR-34a. Serum miR-34a can be a potentially useful diagnostic biomarker of pancreatic ductal adenocarcinoma (73). Furthermore, miR-34a is likely to be involved in the treatment response of lung metastases of HCC to sorafenib (74).…”
Section: Gc-related Mirnasmentioning
confidence: 99%